2009
DOI: 10.1007/s10646-009-0359-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intersex in male clams Scrobicularia plana in the Guadiana Estuary (Portugal)

Abstract: Endocrine disrupting chemicals (EDCs) known to be present in the marine environment, have great potential to influence reproductive status in aquatic organisms. A widespread incidence of intersex linked with EDCs exposure has been reported in molluscs and fish species. The species Scrobicularia plana is inherently gonochoristic; nonetheless, the feminisation of male clams was described in estuaries from the United Kingdom. Thus, this study reports the presence of oocytes in the testis of male clams of S. plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Other animals can be affected, including bivalves that are utterly important for the local economy. Not far from the Ria Formosa, feminization phenomena in clams, Scrobicularia plana, were recently reported (Gomes et al 2009). Besides, since it exits a possible linkage between these chemicals and several human endocrine disorders (Safe 2000), the local condition of Ria Formosa is endanger since the assayed areas are considered clean zones, accordingly to the Directive 76/160/CEE and the Portuguese legislation (DR No.…”
Section: Natural and Pharmaceutical Estrogensmentioning
confidence: 99%
“…Other animals can be affected, including bivalves that are utterly important for the local economy. Not far from the Ria Formosa, feminization phenomena in clams, Scrobicularia plana, were recently reported (Gomes et al 2009). Besides, since it exits a possible linkage between these chemicals and several human endocrine disorders (Safe 2000), the local condition of Ria Formosa is endanger since the assayed areas are considered clean zones, accordingly to the Directive 76/160/CEE and the Portuguese legislation (DR No.…”
Section: Natural and Pharmaceutical Estrogensmentioning
confidence: 99%
“…High incidences of intersexuality has been reported in the estuarine clam Scrobicularia plana in some UK estuaries as well as those in Portugal and Northwest France (Chesman and Langston, 2006;Gomes et al, 2009;Langston et al, 2007;Tankoua et al, 2012). S. plana is normally thought to be gonochoristic but at some UK sites, two-thirds of the clam population was intersex and this condition appeared to arise from a feminization or demasculinization of the male clams.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations at thirteen estuaries in NW France (including 3 sites very close to those in the present study) showed intersex in all populations sampled, with maximum incidences of >50% of the male population affected (Tankoua et al, 2012) comparable to the most impacted populations in the present study. Similarly, intersex in male clams from a single site in the Guadiana estuary in Southern Portugal varied between 5.9% and 71% during 2007 (Gomes et al, 2009). Clearly, the occurrence of intersexed male S. plana is a widespread and consistent feature at many locations within the Channel region.…”
Section: Discussionmentioning
confidence: 89%
“…Further experimental studies revealed that ovotestis in S. plana was indeed a feminization phenomenon and could be induced by exposure to sediments spiked with natural and synthetic oestrogens and alkylphenols (Langston et al, 2007). Since its initial observation in the Avon Estuary, intersex has also been reported in S. plana from Mweeloon Bay, Galway (Raleigh and Keegan, 2006); the Guadiana Estuary, Portugal (Gomes et al, 2009); and 13 estuaries in NW France (Tankoua et al, 2012).…”
Section: Introductionmentioning
confidence: 99%